2013
DOI: 10.7205/milmed-d-12-00493
|View full text |Cite
|
Sign up to set email alerts
|

ANAM4 TBI Reaction Time-Based Tests Have Prognostic Utility for Acute Concussion

Abstract: The Concussion Restoration Care Center has used the Automated Neuropsychological Assessment Metrics version 4 Traumatic Brain Injury (ANAM4 TBI) battery in clinical assessment of concussion. The study's aim is to evaluate the prognostic utility of the ANAM4 TBI. In 165 concussed active duty personnel (all ultimately returned to duty) seen and tested on the ANAM4 TBI on days 3 and 5 (median times) from their injury, Spearman's ρ statistics showed that all performance subtests (at day 5) were associated with few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…This may need to be given additional interpretive weighting, as a growing body of literature has indicated that ANAM reaction time-based subtests may be the most sensitive indicators for determining postinjury changes in neurocognitive functioning. 16,18,20,21,[28][29][30][31] This study was designed using the strengths of each of the aforementioned studies. The primary aim of this study was to estimate RC parameters from a sample of healthy SMs that could be used by clinicians for postdeployment screening purposes.…”
mentioning
confidence: 99%
“…This may need to be given additional interpretive weighting, as a growing body of literature has indicated that ANAM reaction time-based subtests may be the most sensitive indicators for determining postinjury changes in neurocognitive functioning. 16,18,20,21,[28][29][30][31] This study was designed using the strengths of each of the aforementioned studies. The primary aim of this study was to estimate RC parameters from a sample of healthy SMs that could be used by clinicians for postdeployment screening purposes.…”
mentioning
confidence: 99%
“…Reaction time has been used as one of the few neurobehavioral indices for quantifying mTBI sequelae (75, 76, 78, 109) and has been proposed as prognostic utility for acute mTBI (115, 116). In our neuronal network model, reaction time was approximated by the population response time, which was defined as the time at which the model network exhibited maximal response to attention-like stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the ANAM TBI battery as a neuropsychological assessment tool was a weakness of the study. Although there is a body of evidence that lends support to its use in mTBI assessment and other settings there is also literature cautioning its use [6,37,44,49,63]. For example, ANAM instructions are documented to be confusing for elderly demented populations.…”
Section: Limitationsmentioning
confidence: 94%
“…Used synonymously by clinicians in the US Department of Defense, US Department of Veterans' Affairs and many academic settings, concussion/mTBI is defined as a closed-head injury with normal structural imaging, a loss of consciousness (LOC) of no more than 30 minutes and/or alteration of consciousness or post-traumatic amnesia of no more than 24 hours [3,4]. In samples of patients with combat-related mTBIs from OEF/OIF, most mTBIs were caused by blast over-pressure from detonation of improvised explosive devices (IED) [5,6]. Combat blast or IED-related mTBI has been researched [7][8][9][10], but clinically-derived research in the acute phase (i.e.…”
Section: Introductionmentioning
confidence: 99%